Recent studies to validate and compare atmospheric dispersion models for regulatory purposes in the UK. (1st January 2000) - Timmis, R.; Wilkinson, S.; Carruthers, D.J.; McHugh, C.A.
Some results are presented for recent studies to develop new approaches for (i) validating atmospheric dispersion models using crosswind concentration transects, and (ii) summarising and comparing the predictions of models across a range of efflux and meteorological conditions.